Nationally Appropriate Mitigation Action (NAMA) for sustainable cattle ranching in Colombia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
The NAMA for sustainable cattle ranching in Colombia is a public policy that aims to reduce GHG emissions generated by the meat and milk supply chains (mainly beef and dairy).